Floristc evaluation of limestone extraction area in the city of Uberaba / MG, Brazil - Costa, William Raimundo; Gomes Júnior, Juarez Antônio; Sbroia Neto, Raul; Freitas, Marco Túlio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Was studied the floristic composition of the mining area between the cities of Uberaba/ MG, Uberlândia/ MG, with the purpose of identifying biodiversity in the face of activities undertaken at the area. Was registered a hundred species of trees, distributed in forty-three families, the most abundant was Fabaceae. It was concluded that the activities undertaken at the area, while potentially degrading, has not interfered significantly in natural ecological processes.